(untitled) (Pulse, 2023)
Pineal region tumors constitute about 0.4%-1% of intracranial tumors in adults. These tumors may arise from pineal gland itself or structures around it which are all termed as pineal region tumor. Papillary tumor of the pineal region is a non-parenchymal tumor of the pineal region. First described in 2003, it is an extremely rare tumor. We have presented a case of 27-year-old female patient presented as a pineal tumor. After successful excision, the tumor proved to be Papillary tumor of Pineal region (PTPR) both histomorphologically and immunohistochemical study. Pulse Volume 12-14 2020-2022 p.13-15